Effects of flavonol quercetin on syndrome of endogenous intoxication in experimental periodontitis - Andrii Demkovych; Vitaliy Shcherba; Olha Yaremchuk; Halyna Stoikevych; Volodymyr Machogan; Vitalii Luchynskyi (Pensoft Publishers, 2021)
The article presents the results of study effect of quercetin on the indicators of endogenous intoxication syndrome under conditions of experimental periodontitis. One of the key links in the pathogenesis of any inflammatory disease, including maxillofacial area, is endogenous intoxication, an important pathophysiological mechanism of which is the activation of lipid peroxidation. The experimental animals were treated by intramuscular injections with water-soluble quercetin for 7 days. For further research the blood serum was selected in which was determined the content of middle molecular weight molecules and erythrocyte intoxication index. Excessive lipoperoxidation was accompanied by accumulation of peroxidation products and depletion of antioxidant reserves, which led to accumulation of toxic substances. That is why the study of the level of middle molecular weight molecules and erythrocyte intoxication index in simulated bacterial-immune periodontitis is a reliable criterion. Quercetin was able to reduce the expression of endogenous intoxication syndrome in experimental bacterial-immune periodontitis.